Inteligencia de género para la escuela. Las paradojas de la coeducación - Gordillo Cisneros, Enrique G. (2019)
One of the major struggles in Western societies is the pursuit of gender equality, particularly with the aim of eliminating the gap that many observers agree places women at a disadvantage in relation to men. One of the principal arenas in this process—as in similar social transformations—has been education. Indeed, one of its symbolic achievements has been equal educational opportunities for women, especially through the widespread expansion of coeducation (or mixed education) in recent decades (Riordan, 2011). However, could it be that this very model of coeducation constitutes an obstacle to the intended goals? Might this hard-won space become a setting in which gender stereotypes flourish, thereby exacerbating the problem? This is precisely the issue explored in the brief yet thought-provoking book Inteligencia de género para la escuela. Las paradojas de la educación, by Jaume Camps i Bansell, a Spanish educator specializing in the sociology and psychology of education.